R-warfarin clearances from plasma associated with polymorphic cytochrome P450 2C19 and simulated by individual physiologically based pharmacokinetic models for 11 cynomolgus monkeys. (1st February 2018) - Utoh, Masahiro; Kusama, Takashi; Miura, Tomonori; Mitsui, Marina; Kawano, Mirai; Hirano, Takahiro; Shimizu, Makiko; Uno, Yasuhiro; Yamazaki, Hiroshi
Abstract: 1. Cynomolgus monkey cytochrome P450 2C19 (formerly known as P450 2C75), homologous to human P450 2C19, has been identified as R -warfarin 7-hydroxylase. In this study, simulations of R -warfarin clearance in individual cynomolgus monkeys genotyped for P450 2C19 p.[(Phe100Asn; Ala103Val; Ile112Leu)] were performed using individual simplified physiologically based pharmacokinetic (PBPK) modeling. 2. Pharmacokinetic parameters and absorption rate constants, volumes of the systemic circulation, and hepatic intrinsic clearances for individual PBPK models were estimated for eleven cynomolgus monkeys. 3. One-way ANOVA revealed significant effects of the genotype ( p  < 0.01) on the observed elimination half-lives and areas under the curves of R -warfarin among the homozygous mutant, heterozygous mutant, and wild-type groups. R -Warfarin clearances in individual cynomolgus monkeys genotyped for P450 2C19 were simulated by simplified PBPK modeling. The modeled hepatic intrinsic clearances were significantly associated with the P450 2C19 genotypes. The liver microsomal elimination rates of R -warfarin for individual animals after in vivo administration showed significant reductions associated with the genotype ( p  < 0.01). 4. This study provides important information to help simulate clearances of R -warfarin and related medicines associated with polymorphic P450 2C19 in individual cynomolgus monkeys, thereby facilitating calculation of the fraction of hepatic clearance.